Search for the direct production of charginos and neutralinos in final states with tau leptons in √s = 13 TeV pp collisions with the ATLAS detector - Alconada Verzini, María Josefina (2018)
A search for the direct production of charginos and neutralinos in final states with at least two hadronically decaying tau leptons is presented. The analysis uses a dataset of pp collisions corresponding to an integrated luminosity of 36.1 fb-1, recorded with the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of 13 TeV. No significant deviation from the expected Standard Model background is observed. Limits are derived in scenarios of χ˜1+ χ˜1- pair production and of χ˜±1 χ˜02 and χ˜+1 χ˜-1 production in simplified models where the neutralinos and charginos decay solely via intermediate left-handed staus and tau sneutrinos, and the mass of the ˜L state is set to be halfway between the masses of the χ˜±1 and the χ˜01. Chargino masses up to 630 GeV are excluded at 95% confidence level in the scenario of direct production of χ˜±1 χ˜-1 for a massless χ˜01. Common χ˜±1 and χ˜02 masses up to 760 GeV are excluded in the case of production of χ˜±1 χ˜02 and χ˜+1 χ˜-1 assuming a massless χ˜±1. Exclusion limits for additional benchmark scenarios with large and small mass-splitting between the χ˜±1 and the χ˜01 are also studied by varying the ˜L mass between the masses of the χ˜±1 and the χ˜01.